Employees’ attitude towards Islamic banking: Measurement development and validation - Ali, Syed Ahmad; Hassan, Arif; Juhdi, Nurita; Razali, Siti Salwani (Emerald, 2018)
Purpose – Despite widespread acceptance and exponential growth of Islamic banking acrossmany countries, research indicates some critical issues that can potentially downturn this industry. Literature suggests that like other stakeholders such as customers, some employees too have ambivalent attitude towards its concept and practices. This calls for an empirical assessment. As no such comprehensive instrument was available, this study aims to develop a scalemeasuring employees' attitude towards Islamic banking. Design/methodology/approach – This scale development process begins with literature review pertinent to employees’ perspective in Islamic banking, followed by a series of steps critical to achieve robustness and to ensure validity and reliability of the instrument. Research methods include a detailed set of qualitative interviews, content validation, pilot testing and exploratory factor analysis with subsequent confirmatory factor analysis. Findings – The final scale embodies five orthogonal dimensions: awareness of Islamic banking, usefulness of Islamic banking, perception of Shariah compliance, patronage towards Islamic banking and attractiveness towards Islamic banking. Research limitations/implications – This instrument may be used both by research scholars and practicing managers to measure employees’ attitude towards Islamic banking system and practices. It may also serve as a diagnostic tool to identify the areas of strength and weaknesses in the Islamic banking system as perceived by the employees themselves. Originality/value – An instrument to measure employees’ attitude towards Islamic banking system is much needed as no such comprehensive instrument is available to the best of authors’ knowledge. The study attempts to fulfil this need.